Correspondence Between Reliability of Rental Flat Building and Space Needs - Rita Laksmitasari Rahayu; Huri Suhendri; Rimsa Rusmiland; Indah Yuliasari (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
Flats for rent need to be designed so that residents move comfortably and can save themselves in times of disaster. This research was conducted with the aim of knowing the spaces needed by the occupants by taking into account the reliability of the building-safety and comfort. Some aspects of building reliability are motion comfort and safety. Data was collected by an online questionnaire, which was distributed to residents using non-random sampling. The collected text data was analyzed by content analysis. From the results of the analysis revealed that residents tend to be comfortable moving in rental residential units. Residents need a secondary space that is a shelf and work space. Storage space represents the meaning of storage of small items. Work, study and storage of equipment represent the meaning of workspace needs. Residents need some secondary space in a residential unit that has aspects of motion comfort and security during disaster evacuation. Motion comfort mainly represents a little furniture, has storage space, and doesn't interfere with activities like sitting and watching television. The number of residents felt safe moving when disaster evacuation in vertical housing was almost the same as the number of residents who felt the evacuation route was not ideal. Easy access is achieved, wide circulation room, near the emergency stairs is represented by the meaning of feeling safe moving during a disaster evacuation. There is no special emergency ladder, narrow circulation space, the condition of a damaged staircase at the time of disaster evacuation is represented by meaning not ideal. This study found a significant relationship between the reasons for motion comfort and the presence of space requirements. There is no significant relationship between disaster evacuation security and secondary space requirements.